The bricklayer [videorecording (Blu-Ray)] - Lindsay, Paul (Vertical, 2024)
When a rogue insurgent blackmails the CIA by assassinating foreign journalists and framing the government, the agency must lure its most brilliant yet rebellious operative out of retirement to unravel the international conspiracy.